Podomačena tuja zemljepisna imena v slovenskih atlasih sveta - Kladnik, Drago (Geografija Slovenije, 2007)
This study presents various aspects of the use of adapted exonyms (i.e., foreign geographical names) in Slovenian. The cartographic use of these names rests on a long tradition dating back nearly a century and a half. This study presents the issues related to the use of adapted exonyms in all major Slovenian world atlases, including the Veliki splošni leksikon (Large General Encyclopedia) and the dictionary section of the latest Slovenski pravopis (Slovenian Normative Guide). Adapted exonyms are treated based on their regional affiliation and semantic type and, for names in the four most prominent atlases, the typology of Slovenianized exonyms has been redesigned and studied with regard to level and type of adaptation. The use of adapted exonyms in the individual sources treated is critically discussed, enabling an onomastic understanding of their actual value and reliability. The collected material is a basis for the greatly needed standardization of adapted exonyms, as recommended by the resolutions of the United Nations Conference on the Standardization of Geographical Names. These resolutions consistently demand that individual UN member states limit the use of exonyms, which to some degree contradicts the principle of linguistic autonomy.